Breast feeding and Immunization practices soon after birth - A hospital based study - Kapil Gandha; Mukeshgiri Goswami (Medsci Publications, 2018)
Background: World over most newborn death occurs within the first week of delivery. To prevent neonatal death early postnatal care advice and correct practices are key to detect early morbidity and avert death. This study evaluated feeding practice and other preventive practices for new born in district hospital. Methods: A cross sectional analytical study was done during pe- riod of April 2016 to June 2016. Total 195 postnatal women in postnatal ward were the participants. Data was collected by pre formed semi structured questionnaire, entered and analyzed by Microsoft excel 2007. Result: Only 31.79% had started breast feeding within 1 hour of delivery and 60.51% had started within 1-24 hour of delivery. 33.85% gave pre lacteal feed to their new born child. 27.69% did not give colostrum, 87.69% was not advised for KMC. 66.15% knows about correct frequency of breast feeding by advice of doc- tor and staff nurse. 40% were not advised for birth hepatitis B vac- cine, 35.38% were not counseled regarding exclusive breast feed- ing. 23.08% had less than 4 ANC visit. Conclusion: KMC, initiation of breast feeding, colostrum should be emphasized in counselling. Training gap amongst health care functionaries at various level must be dealt with on urgent basis.